Increasing role of municipalities in social policy in Turkey: The case of Istanbul metropolitan municipality in the last decade - Aysan, Mehmet Fatih (My University, 2006)
Bu tezin amacı iki temel boyutta sınıflandırılabilir. İlk olarak, sosyal politikaları analiz etmek için Türkiye’deki ve Dünyadaki sosyo-ekonomik yapısal dönüşümü incelemek. İkinci olarak ise belediyelerin sosyal politika alanındaki artan rollerini İstanbul Büyükşehir Belediyesi’nin son on yılında incelemektir. Gosta Esping-Andersen tarafından çıkarılan ve Güney Avrupa refah rejimi üzerine çalışanlar tarafından geliştirilen refah rejimi tipolojisi tezin teorik çerçevesini oluşturmakta faydalanılmıştır. Tezde Türkiye’deki sosyo-ekonomik yapının değişmesiyle birlikte, 1990’lı yılların ortalarından beri İstanbul Büyükşehir Belediyesi’nin özellikle sosyal yardım ve sosyal hizmet alanında sosyal politika rolünün arttığı gösterilmektedir. Fakat bu sosyal politikalar, belediye tarafından uygulanan geçici ve toplumun tüm kesimine hitap etmeyen “mikro sosyal politika”lardan oluşmaktadır.

The objective of this thesis can be categorized under two dimensions. Firstly, to analyze the social policies this thesis evaluates socio-economic transformations as a series of structural changes in the world as well as in Turkey. Secondly, it examines the increasing role of municipalities in social policies in the last decade in the case of Istanbul Metropolitan Municipality in Turkey. The welfare regime typology introduced by Gosta Esping-Andersen and expanded by researchers who work on Southern European welfare regime is very helpful for the theoretical framework of the study. The research mainly includes social assistance and social services of Istanbul Metropolitan Municipality in last decade. In this research it is shown that with the transformation of socio-economic structure, the roles of Istanbul Metropolitan Municipality in social policy, especially in social assistance and social services, have changed since mid-1990s. The new social policies, however, have been composed by temporary and micro solutions and they have not been comprehensive.
Keywords: Belediyeler_Sosyal Politika; Sosyal Politika_Türkiye